The influence of home environment on 2-year-old Chinese children's language development: the mediating effect of executive function and the moderating effect of temperament - Qiu, Siyao; Wang, Zhidan (Frontiers in Psychology, 2024)
Prior research highlighted the effect of home environment on the language development of young children. Recent research has mainly discussed the moderating effect of personality traits like temperament. Nevertheless, the precise mechanism about the relationship between home environments to children's language development remains incompletely understood. This study explored how home environment impacts the language development of 2-year-old toddlers and the role of temperament and executive function in this relationship. We used the Chinese Child Adaptive Behavior Scale, the Temperament Scale for 1–3 years old of toddlers and the Home Environment Scale for Infants' and Toddlers' families to assess children's language development, temperament, and home environment. Simultaneously, the research used the Stroop-like day-night task and the multiple location search task to evaluate children's executive function. A total of 117 2-year-old children as well as their parents were involved in the study. The results revealed that home environment significantly predicts children's language ability with executive function as a mediating role. Temperament dimensions including extraversion, independence, reactivity, and social inhibition play a moderating role between home environment and executive function. The findings contributed to the improved implementation of home education tailored to children with different temperament traits, offering effective support for the cognitive and language development of young children.